Analisis Korelasi Kematian Neonatal BBLR: Cakupan Tablet Tambah Darah Ibu Hamil dan Kunjungan K4 di Jawa Timur (Periode 2019-2021) - Nabilla Nuraeni; Lucia Yovita Hendrati (Universitas Airlangga, 2023)
Background: Neonatal death is a condition responsible for babies' deaths during the first month after birth (0-28 days). Low birth weight (LBW) conditions are the leading cause of neonatal death. Nutritional needs during pregnancy can reduce the risk of LWB neonatal death. One way to avoid it is to take iron-folic acid tablets during pregnancy. Health conditions must be monitored during pregnancy to reduce the risk of neonatal death by conducting four ANC. East Java is one of the largest contributors to LWB neonatal death in Indonesia 2019-2021. Objectives: This study aimed to analyze the relationship of LWB neonatal death with the coverage of iron-folic acid tablet pregnancy and four ANC in East Java. Methods: This study used an observasional analytic study design with 38 cities/regencies in East Java. The Pearson correlation test was used to analyze secondary data from the East Java Health Report for 2019-2021. Data processing was done using SPSS 18. Results: The results of this study show that the neonatal death rate in East Java continues to decrease from 2091-2021. The the coverage of iron-folic acid tablet pregnancy was largest in 2019 (92%) and lowest in 2020 (88.5%). Four ANC coverage was the largest in 2019 (91.2%) and the lowest in 2020 (90%). There was no significant correlation between iron-folic acid tablets of pregnant women coverage and cases of neonatal death from LBW in 2019 (p = 0.504; r = -0.112), whereas there was a significant correlation between four ANC coverage and neonatal death cases due to LBW in 2019 (p = 0.001; r = -0.497). Conclusions: The coverage of iron-folic acid tablets was not associated with the incidence of LWB neonatal death but with four ANC coverage. Educating people about the importance of four ANC during pregnancy is essential to prevent neonatal death.